Jean-Jacques Rousseau on the individual and society - Perkins, Merle L. (Studies in Romance languages (Lexington, Ky.), 1974)
In this study, Merle L. Perkins links individual freedom with national power in offering a close reading of Jean-Jacques Rousseau's major texts. He sees in Rousseau's thought an extreme tension and interdependence between the idiosyncrasy of nonconforming character and an almost obsessive concern with the external pressures operating on the state.